The Female Sex Confers Different Prognosis in Heart Failure: Same Mortality but More Readmissions - López-Vilella, Raquel; Marqués-Sulé, Elena; Laymito Quispe, Rocío del Pilar; Sánchez-Lázaro, Ignacio; Donoso Trenado, Víctor; Martínez Dolz, Luis; Almenar Bonet, Luis (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Heart failure (HF) is a major cause of morbimortality both in men and women. Differences between sex in etiopathogenesis, response to treatment, and quality of care have been found in patients with HF. Females are usually under-represented in clinical trials and there is no solid evidence demonstrating the influence of sex in the prognostic of chronic HF. The primary objective of this study was to analyse the differences in mortality and probability of hospital readmission between males and females with HF. The secondary objective was to compare mortality and probability of hospital readmission by ejection fraction (reduced vs. preserved). Methods: Patients with decompensated HF that were consecutively admitted to a Cardiology Service of a tertiary hospital for 4 years were recruited. De novo HF, death during hospitalization, programmed admissions and those patients with moderate left ventricular ejection fraction (LVEF) (40–50%) were discarded. Finally, 1,291 patients were included. Clinical profiles, clinical history, functional status, treatment at admission, first blood analysis performed, readmissions and mortality at follow-up were analyzed and compared. All patients underwent an echocardiographic study at admission. HF with reduced ejection fraction (HFrEF) was considered when left ventricular ejection fraction (LVEF) was <40%, whilst HF with preserved ejection fraction (HFpEF) was considered when LVEF was ≥50%. Results: 716 participants were male (55%). Basal characteristics showed differences in some outcomes. No differences were found in probability of survival among patients with decompensated HF by sex and ejection fraction (p = 0.25), whereas there was a clear tend to a major survival in females with HFrEF (p < 0.1). Females presented more readmissions when compared to males, independently from the LVEF (females = 33.5% vs. males = 26.8%; p = 0.009). Adjusted multivariate analysis showed no association between sex and mortality (HR = 0.97, IC 95% = 0.73–1.30, p = 0.86), although there was association between female sex and probability of readmission (OR = 1.37, IC 95% = 1.04–1.82, p = 0.02). Conclusions: Sex does not influence mid-term mortality in patients admitted for decompensated HF. Nevertheless, probability of readmission is higher in females independently from LVEF. Thus, it should be considered whether healthcare may be different depending on sex, and a more personalized and frequent care may be recommended in females.